IMPLEMENTATION OF THE VILLAGE ASSET MANAGEMENT SYSTEM (SIPADES) IN TAMBAK KALISOGO VILLAGE - Akhsanur Rizqi, Muhammad Aqil; Mursyidah, Lailul (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This research examines the implementation of the Village Asset Management System (SIPADES) in Tambak Kalisogo Village. The purpose of this study is to determine how the village asset management system (SIPADES) is implemented in Tambak Kalisogo Village. The research method used is a qualitative approach with descriptive analysis, using Edward III's policy implementation theory (1980) involving four main indicators, namely communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of (SIPADES) in Tambak Kalisogo Village has not been fully optimized. Ineffective communication, minimal socialization regarding system updates, and poor monitoring by relevant agencies are the main obstacles. However, competent human resources and adequate facilities support the success of this system. To improve the implementation of the Village Asset Management System (SIPADES), ongoing technical guidance, more intensive monitoring, and improved coordination between village governments and relevant agencies are needed.